PENERAPAN PROTOKOL KESEHATAN DALAM RANGKA PENCEGAHAN PENULARAN COVID 19 DI TPQ MADIN BAITULLAH - Muhammad Fatchur Rochim; Holilah Holilah (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2022)
Covid-19 or Corona Virus Disease 2019 is a disease caused by a new type of virus found in Wuhan, China. Transmission of this virus is growing very rapidly throughout the world starting from God, to all over China, and spread very quickly throughout the world, not least in Indonesia. More and more impacts are happening because of Covid 19, one of which is the implementation of health protocols in public places, markets, and educational institutions. In order to standardize health protocols for educational institutions of worship, researchers make the TPQ Madin Baitullah a reference and source of analysis of the Application of Health Protocols in the educational institutions. This is on the grounds that the TPQ Madin Baitullah institution is still active in conducting face to face learning activities even though the location of the institution is in the Purabaya Bungurasih terminal environment. Researchers used qualitative research methods with data collection techniques through interviews and direct observation at the TPQ Madin Baitullah this was done because, with direct interviews, researchers were more easily obtained data.From the results of interviews and observations researchers concluded that there are 7 things that must be done by the TPQ Madin Baitullah management as an initial effort to Prevent Corona 19 Virus first., thoroughly cleaning the TPQ Madin Baitullah and spraying disinfectant liquid, providing a Handsanitaizer or washing place, and finally checking the temperature of the worshipers who will attend the prayers at the and finally shorten the time of worship activities at the TPQ Madin Baitullah.